Distribution of dust properties around carbon rich AGB star: IRAS 04427+4951 using IRIS and AKARI survey - Upadhyay, Devendra Raj; Subedi, Trishna (BIBECHANA, 2021)
Interstellar dust properties using far-infrared bands analyze nature around asymptotic giant branch stars and stellar objects. Here, we present physical properties around the cavity region across an AGB star named IRAS 04427+4951 Sky View Observatory of IRIS, AKARI map, SIMBAD, Aladin v2.5, and Gaia Archive. The average color temperature and mass are 23.48 ± 0.009 K, 3.55×1027 kg (1.79× 10-3 Mʘ ) in IRIS data and 14.89 ± 0.004 K and 5.34×1028 kg (2.69 × 10-2 Mʘ ) from AKARI data. The size of isolated cavity-like structure around the AGB stars of 45.67 pc × 17.02 pc and 42.25 pc × 17.76 pc, respectively. The visual extinction is to be in the range of 3.2×10-4 to 4.3×10-4 mag in and 4.5 × 10-3 to 7.4×10-3 mag. The inclination angle is 86.150 and 93.920. The method and results we present developed can for the study of astrochemistry of interstellar medium. BIBECHANA 18 (2) (2021) 154-163